"It shows we felt safe because a few of us had tears": Exploring how perceptions of the group space can influence experiences of parenting programmes. (November 2021) - McKay, Kathy; Kennedy, Eilis; Ranieri, Veronica; Young, Bridget
Abstract: How parents navigate the physical, social, and emotional geographies of parenting groups, particularly when considering safe and unsafe spaces, has been little studied. This paper examines how a parent's perception of a parenting programme as a safe or unsafe landscape influenced whether they completed the programme or dropped out. Transcripts from interviews with 42 parents who had attended a parenting programme, primarily a recent Incredible Years (IY) group, were thematically analysed. We describe parents' narratives in terms of four main themes: 1. The group as a safe space; 2. Composition of the group matters; 3. How a parent is referred matters; and, 4. The group as an unsafe space. Parents' perceptions of whether a group space felt safe and cohesive (or not) were key influences on whether they attended the group at all, whether they continued attending, and for those who did continue, whether they felt IY was beneficial. Examining how parents navigated a parenting group space has highlighted the importance of emotional safety and connections to the facilitator and other group members, and the role of good facilitation in fostering safety and connection for parents. Our findings also indicate the importance of exploring parents' experience of a group throughout the programme and allowing them to leave a group that does not feel safe. Highlights: Parenting groups can be beneficial but need to provide a safe space for parents. Parents often come to parenting groups feeling stigmatised and downtrodden. Non-judgmental group facilitation can make parents feel listened to and valued. Parents who were able to make positive changes felt supported by their group. More care needs to be taken when making a group as composition impacts experience.